China after the pandemics: How to survive international scepticism and domestic distrust? - Costa, C. M. (The world before and after Covid-19: Intellectual reflections on politics, diplomacy and international relations, 2020)
Even six months after its outbreak, nobody yet knows the real impact that Covid-19 will have on human behaviour, societies and politics. People struggle worldwide to make sense of a challenge of such magnitude that it affects the way they work, conduct their relationships with family and friends, and organise their life safely. Above all, people expect to get back to their ‘normal’ life with a sense of security. While rationality pushes for solutions and alternative models of behaviour at the individual, national and international level, instinct drives the search for culprits, to identify who is responsible for this pandemic. If emotional reactions prevailed over an analytical and rational assessment of the situation, then disinformation, fake news and propaganda could find a fertile ground and even turn into a threat for both domestic stability and international peace. The choice of a rational approach largely depends on how political leaderships and national institutions look at this new context.